Key elements for promoting public-private partnerships in research and innovation - Shem Sikombe; Franco Muleya; Joseph Phiri; Sambo Zulu; Peter Simasiku; Mercy Situtu (Cogent Business & Management, 2024)
Public-private partnerships have been widely applied in financing infrastructure development with mixed results. Research calls to extend public-private partnerships to research and innovation to foster strategic linkages between research and industry have been increasing. This study seeks to investigate key elements for promoting public-private partnerships in research and innovation using evidence from research institutions. The research study followed an explorative design, and 19 purposefully selected respondents from research and development institutions and universities were interviewed. The findings reveal different forms of research collaboration through memoranda of understanding. The best practices for promoting public-private partnerships in research and innovation are enhancing the attractiveness of the partnering institutions and establishing innovation hubs and intellectual property policies. The elements for effectively implementing public-private partnerships in research and innovation include a supportive regulatory framework, joint financing of research equipment and tax incentives for research equipment. Priority sectors for promoting public-private partnerships in research and innovation include energy, agriculture, waste management, engineering and technology and environmental sustainability. This study is one of the first to investigate the key elements for promoting public-private partnerships in research and innovation as a mechanism for funding high-impact research in the context of a developing country. Furthermore, the key elements can guide countries wishing to develop frameworks for promoting public-private partnerships in research and innovation.
Keywords: 650; Key elements; public-private partnerships; research and innovation; exploratory study; Zambia